Métodos analíticos para determinação da qualidade do mel por cromatografia líquida acoplada à espectrometria de massas - Patricia Amaral Souza Tette (2016)
Honey, besides being a natural sweetener and energy source, shows immunological effect, antibacterial, antiinflammatory, analgesic, sedative and expectorant activities. The quality of honey can be influenced by several factors, including the presence of chemical contaminants, such as pesticides. In adttition, the characterization of the botanical origin of monofloral honeys is important for product quality, information that ensures authenticity and increases its market value. The aim of this study was to develop and validate methods by LC-MS/MS for the multiresidue analysis of pesticides in honey and also to ensure citrus honey authenticity. The validated method for pesticides determination using a modified QuEChERS technique as sample preparation and UHPLC-MS/MS was suitable for detection and quantitation of 116 pesticides in honey. Recoveries ranged from 81.6 to 108.9%, the detection limitwas 0.005 mg/kg and the limits of quantification were 0.01 and 0.025 mg/kg. Ingeneral, samples of honey showed appropriate quality in terms of pesticideresidues. Only one of the 66 samples from Minas Gerais, had trichlorfon at 0.029 mg/kg. For authenticity of citrus honey, the use of synephrine, a bioactive amine tipically found in citrus species, was proposed. The developed HPLCMS/MS method was optimized and validated and presented limits of detectionand quantification of 0.66 ng/g and 1 ng/g, respectively, and recoveries between74.3 and 90.7%. Synephrine was detected in samples with some contribution ofcitrus flowering and therefore this amine can be used as an indication of presence of citrus species in honey samples. The origin of honey was also determined by qualitative pollen analysis to confirm the presence of citrus.